ANALISIS KONSEP NGUNDA BAYU PADA TARI REJANG DESA, DI DESA TISTA, KECAMATAN ABANG, KABUPATEN KARANGASEM, BALI - Santi Sukma Melati, Ni Ketut; Tampubolon, Rines Onyxi; Maharani, Lissa; Radiana Putra, I Gede; Bang Sada Graha Saputra, I Putu Bagus (Jurnal Pendidikan Tari, 2025)
The Rejang Desa dance has become an important cultural heritage in Tista Village, Abang District, Karangasem Regency. This dance is characterized by its distinctive and classical makeup and costume design, which continue to uphold local wisdom as the central element of their aesthetic arrangement. Rejang Desa can only be performed and appreciated during the Kuningan and Manis Kuningan ceremonies, making it distinct from Rejang Dewa, which may be performed in various religious ceremonies across different villages. The term dance is inseparable from the concept of movement technique, as every dance composition employs movement as its primary medium of expression. In dance movements, the control of breath and energy is essential to maintain the integrity and fluidity of motion. This understanding is commonly referred to as the Ngunda Bayu technique, which is an inherent practice among Balinese dancers across various dance forms. Therefore, this study aims to examine and understand the application of the Ngunda Bayu concept in the Rejang Desa dance of Tista Village. The presence of this concept can be observed through the duration of the performance and the structure of the presentation. To explore this issue, a qualitative research method is employed, supported by the theory of form. It is expected that the findings of this research will reveal and substantiate the use of the Ngunda Bayu concept within the Rejang Desa dance of Tista Village. In line with this objective, the author seeks to develop a scientific discussion that examines the embodiment of Ngunda Bayu in the performance of Rejang Desa in Tista Village.